Comparison of Seismic Performance of L-Shaped Multi-Story Structures with Eccentrically Braced Frame and Friction Dampers - Andhika Daffa Ramadhan; Roro Sulaksitaningrum; I Putu Ellsa Sarassantika; Cintantya Budi Casita (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2025)
At the stage of planning the design of an asymmetric multi-story structure, the seismic performance of the structure must be considered, especially in earthquake prone areas. A structure can increase its capacity to withstand seismic loads by using an appropriate bracing system, such as eccentric bracing or utilizing seismic dampers like friction dampers. This research aims to compare five L-shaped multi-story steel structural models using Eccentrically Braced Frame and friction dampers. The models that focus of this research are model 1 (Moment Resisting Frame), model 2 (structure with diagonal EBF), model 3 (structure with inverted V EBF), model 4 (structure with diagonal friction damper), and model 5 (structure with chevron friction damper). To analyze each model from the elastic condition to the collapse condition, the ETABS software was used, which employs a nonlinear static pushover approach. As a result, all evaluated structural models meet the Immediate Occupancy performance level, which means that all five models can still function normally even after an earthquake occurs. Because of the higher ductility capacity and better inelastic behavior compared to MRF and EBF structures, structures with friction dampers are the best choice for use in steel structures.